Thermal via allocation for 3-D ICs considering temporally and spatially variant thermal power - Yu, Hao (2010)
The existing 3-D thermal-via allocation methods are based on the steady-state thermal analysis and may lead to excessive number of thermal vias. This paper develops an accurate and efficient thermal-via allocation considering the temporally and spatially variant thermal-power. The transient temperature is calculated